Asymmetric porous double-layer composite hydrogel as well as preparation method and application thereof
By developing asymmetric porous double-layer composite hydrogels, combined with polyvinyl alcohol and activated carbon, the foreign body reaction and rapid degradation of polymer materials in abdominal wall defect repair was solved, and long-term mechanical support and good biocompatibility were achieved.
Patent Information
- Application Number
- CN202510368777.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Existing polymer materials have problems of foreign body reaction and rapid degradation in the repair of abdominal wall defects, resulting in high recurrence rates and difficulty in providing long-term mechanical support.
Asymmetric porous double-layer composite hydrogel was developed, using polyvinyl alcohol hydrogel layer and activated carbon/polyvinyl alcohol composite hydrogel layer, prepared by freezing and thawing method to form a double-sided asymmetric structure to improve biocompatibility and mechanical properties.
This hydrogel material exhibits good biocompatibility, stability and mechanical properties in biomedical applications, reducing postoperative adhesion problems, and promoting cell proliferation and adhesion through the introduction of activated carbon, and improving anti-swelling performance.
Smart Images

Figure CN119868642A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of surgical biomedical materials, and more specifically, to an asymmetric porous double-layer composite hydrogel and a preparation method and application thereof. Background Art
[0002] Abdominal wall defect is a common disease, and tension-free repair based on polymer materials is the main treatment method. At present, synthetic patches based on polypropylene, polyester, etc. are widely used in abdominal wall defect repair due to their advantages of high mechanical strength and deformation resistance. However, up to 30% of patients with abdominal wall defects have local contamination / infection, and synthetic patches can induce severe foreign body reactions after being implanted in contaminated areas. Biological patches have become the preferred material for repairing contaminated abdominal wall defects due to their excellent biocompatibility and tolerance to contamination. Unfortunately, existing biological patches will degrade rapidly in the body and lose their mechanical properties, and cannot provide biocompatible long-term mechanical support for abdominal wall defect reconstruction, resulting in an extremely high recurrence rate. Secondary surgery is often required to use synthetic patches to effectively reconstruct the abdominal wall. Therefore, how to reduce the foreign body reaction of polymer materials has always been a bottleneck problem in the field of abdominal wall defect repair. Hydrogel materials are most likely to be developed for abdominal wall defect repair materials due to their good biocompatibility and functional diversity. Among them, polyvinyl alcohol (PVA) is a synthetic water-soluble polymer. The polyvinyl alcohol hydrogel formed by the freeze-thaw method has good biocompatibility, excellent stability and physical and mechanical properties. Therefore, it is widely used in biomedical applications such as postoperative adhesion prevention and wound repair. Porous carbon materials are widely used in biomedical fields such as drug loading and adsorption due to their good compatibility and high specific surface area, but have not yet been used in abdominal wall defect repair materials. Although related inventions have used hydrogel materials for abdominal wall defect repair, especially hydrogels with asymmetric porous structures have been proven to have excellent abdominal wall defect repair effects. However, the preparation process of most hydrogel materials is complicated, and solvents or impurity residues are not easy to remove, making it difficult to mass produce, and there is even a risk of inducing severe foreign body reactions; some hydrogel materials also add antibacterial / anti-inflammatory components, which inevitably have certain biological toxicity, and the diversity and complexity of drug-device combination products also increase the difficulty and uncertainty of transformation. Therefore, it remains a huge challenge to introduce porous carbon materials into hydrogels and develop a green, economical, and easy-to-mass-produce method for preparing asymmetric porous composite hydrogels. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies in the prior art and to provide an asymmetric porous double-layer composite hydrogel and a preparation method and application thereof.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: an asymmetric porous double-layer composite hydrogel is provided, wherein the asymmetric porous double-layer composite hydrogel comprises a first hydrogel layer and a second hydrogel layer, wherein the first hydrogel layer is a polyvinyl alcohol hydrogel layer, and the second hydrogel layer is an activated carbon / polyvinyl alcohol composite hydrogel layer; The asymmetric porous double-layer composite hydrogel has a double-sided asymmetric structure, including a loose porous surface and a dense porous surface.
[0005] In the present technical solution, the provided asymmetric porous double-layer composite hydrogel adopts a polyvinyl alcohol hydrogel system, which ensures the overall biocompatibility and good mechanical properties of the composite hydrogel; further, the asymmetric porous double-layer composite hydrogel includes a polyvinyl alcohol hydrogel layer and an activated carbon / polyvinyl alcohol composite hydrogel layer, and the polyvinyl alcohol hydrogel layer provides a dense porous surface, which not only ensures its good biocompatibility, excellent stability and mechanical properties when used as a biomedical material, but also avoids problems such as postoperative adhesion; at the same time, the activated carbon / polyvinyl alcohol composite hydrogel layer provides a loose porous surface, which effectively promotes cell proliferation and adhesion, and the introduction of activated carbon can also effectively remove ROS and improve the anti-swelling properties of the hydrogel.
[0006] Another object of the present invention is to provide a method for preparing an asymmetric porous double-layer composite hydrogel, comprising the following steps: (1) dissolving polyvinyl alcohol in water, and stirring to obtain a polyvinyl alcohol aqueous solution; (2) adding activated carbon to the polyvinyl alcohol aqueous solution and stirring to mix evenly, and freezing to obtain an activated carbon / polyvinyl alcohol composite hydrogel; (3) The activated carbon / polyvinyl alcohol composite hydrogel prepared in step (2) is allowed to stand and melt, and the polyvinyl alcohol aqueous solution is evenly scraped on the surface of the melted activated carbon / polyvinyl alcohol composite hydrogel, and the surface is allowed to stand and level, and then the activated carbon / polyvinyl alcohol composite hydrogel with the polyvinyl alcohol aqueous solution evenly scraped on the surface is repeatedly freeze-thawed, and then freeze-dried and rehydrated in phosphate buffer to obtain an asymmetric porous double-layer composite hydrogel.
[0007] Preferably, the degree of polymerization of the polyvinyl alcohol used in the present technical solution is in the range of 1700-4500, and the degree of alcoholysis is in the range of 97%-99%.
[0008] More preferably, the degree of polymerization of polyvinyl alcohol is 1700 and the degree of alcoholysis is 99%.
[0009] Furthermore, in the step (1), the mass fraction of the polyvinyl alcohol aqueous solution is 5% to 15%.
[0010] Furthermore, in the step (2), the mass ratio of activated carbon to the polyvinyl alcohol aqueous solution is (0.5-2):100.
[0011] Furthermore, in the step (3), the mass ratio of the coated polyvinyl alcohol aqueous solution to the activated carbon / polyvinyl alcohol composite hydrogel is 1:(3-4).
[0012] Furthermore, in the step (1), the mixture is stirred and mixed at 90-100° C. to prepare the polyvinyl alcohol aqueous solution.
[0013] Furthermore, in the step (2), the mesh size of the activated carbon is 100-400 mesh; and the step of stirring and mixing uniformly is: stirring at a speed of 10000-13000 r / min for 10-20 min.
[0014] Preferably, in the step (2), the activated carbon / polyvinyl alcohol composite hydrogel is prepared by freezing at -30 to -10 °C for 10 to 16 hours.
[0015] Preferably, in step (3), the activated carbon / polyvinyl alcohol composite hydrogel prepared in step (2) is melted at 20-30°C for 1-3 h, the polyvinyl alcohol aqueous solution is evenly scraped on the surface of the melted activated carbon / polyvinyl alcohol composite hydrogel, and the mixture is left to level. The activated carbon / polyvinyl alcohol composite hydrogel with the polyvinyl alcohol aqueous solution evenly scraped on the surface is then frozen at -30--10°C for 10-16 h, and then melted at 20-30°C for 1-3 h. The freezing-thawing step is repeated 3-5 times, and then freeze-dried for 22-26 h and rehydrated in phosphate buffer at 20-35°C to prepare the asymmetric porous double-layer composite hydrogel.
[0016] Preferably, in step (3), the mass fraction of the polyvinyl alcohol aqueous solution uniformly coated on the surface of the activated carbon / polyvinyl alcohol composite hydrogel is 5% to 15%.
[0017] Another object of the present invention is to provide an asymmetric porous double-layer composite hydrogel, wherein the asymmetric porous double-layer composite hydrogel is prepared by the preparation method of the asymmetric porous double-layer composite hydrogel described in the technical solution.
[0018] Another object of the present invention is to provide application of the asymmetric porous double-layer composite hydrogel in biomedical materials.
[0019] Preferably, the present invention also provides an application of an asymmetric porous double-layer composite hydrogel in a soft tissue defect repair patch, wherein the soft tissue includes the heart, intestine, artery, lung, stomach, peritoneum, liver and kidney.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides an asymmetric porous double-layer composite hydrogel, which adopts a polyvinyl alcohol hydrogel system to ensure the overall biocompatibility and good mechanical properties of the composite hydrogel; further, the asymmetric porous double-layer composite hydrogel includes a polyvinyl alcohol hydrogel layer and an activated carbon / polyvinyl alcohol composite hydrogel layer, and the polyvinyl alcohol hydrogel layer provides a dense porous surface, which not only ensures its good biocompatibility, excellent stability and mechanical properties when used as a biomedical material, but also avoids problems such as postoperative adhesion; at the same time, the activated carbon / polyvinyl alcohol composite hydrogel layer provides a loose porous surface, which effectively promotes cell proliferation and adhesion. The introduction of activated carbon can also effectively remove ROS and improve the anti-swelling performance of the hydrogel.
[0021] (2) The present invention also provides a method for preparing an asymmetric porous double-layer composite hydrogel, wherein the activated carbon and the polyvinyl alcohol aqueous solution are uniformly mixed and then frozen to obtain the activated carbon / polyvinyl alcohol composite hydrogel, and then the polyvinyl alcohol aqueous solution is uniformly scraped on the prepared activated carbon / polyvinyl alcohol composite hydrogel, and further the freeze-thaw method is used to prepare the asymmetric porous double-layer composite hydrogel. The preparation method is simple and efficient, and at the same time more economical and easy to mass produce, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the asymmetric porous double-layer composite hydrogel PVA / PVA-AC10 prepared in Example 2; Figure 2 The swelling rate curves of the asymmetric porous double-layer composite hydrogels PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 prepared in Examples 1-3; Figure 3 The ROS scavenging curves of the asymmetric porous double-layer composite hydrogels PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 prepared in Examples 1-3; Figure 4 Cell compatibility diagrams of asymmetric porous double-layer composite hydrogels PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 prepared in Examples 1-3; Figure 5 This is a fluorescence image of cell adhesion of the asymmetric porous double-layer composite hydrogel PVA / PVA-AC10 prepared in Example 2; Figure 6 This is a picture of the asymmetric porous double-layer composite hydrogel PVA / PVA-AC10 prepared in Example 2 repairing the abdominal wall defect of a rat. DETAILED DESCRIPTION
[0023] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0024] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0025] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or according to the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels).
[0026] Example 1 This embodiment provides a method for preparing an asymmetric porous double-layer composite hydrogel, comprising the following steps: (1) Add 10 g of polyvinyl alcohol to 90 g of water, stir and mix at 90-100 °C to obtain a 10% polyvinyl alcohol aqueous solution; (2) 0.25 g of medicinal activated carbon was mixed with 50 g of 10% polyvinyl alcohol aqueous solution under high-speed stirring at 12,000 rpm for 15 min, poured into a mold, and frozen at -20 °C for 12 h to obtain activated carbon / polyvinyl alcohol composite hydrogel PVA-AC5; (3) 3 g of activated carbon / polyvinyl alcohol composite hydrogel PVA-AC5 was melted at 20-30 °C for 1-3 h, and then 1 g of 10% polyvinyl alcohol aqueous solution was evenly scraped on the surface of the activated carbon / polyvinyl alcohol composite hydrogel, allowed to stand and level, frozen at -20 °C for 12 h and then melted at 25 °C for 2 h. The freeze-thaw step was repeated 5 times, and then freeze-dried for 24 h and rehydrated in phosphate buffer at 20-35 °C to obtain the asymmetric porous double-layer composite hydrogel PVA / PVA-AC5.
[0027] Example 2 This embodiment is a preferred embodiment, and also provides a method for preparing an asymmetric porous double-layer composite hydrogel, comprising the following steps: (1) Add 10 g of polyvinyl alcohol to 90 g of water, stir and mix at 90-100 °C to obtain a 10% polyvinyl alcohol aqueous solution; (2) 0.5 g of medicinal activated carbon was mixed with 50 g of 10% polyvinyl alcohol aqueous solution under high-speed stirring at 12,000 rpm for 15 min, poured into a mold, and frozen at -20 °C for 12 h to obtain activated carbon / polyvinyl alcohol composite hydrogel PVA-AC10; (3) 3 g of activated carbon / polyvinyl alcohol composite hydrogel PVA-AC10 was melted at 20-30 °C for 1-3 h, and then 1 g of 10% polyvinyl alcohol aqueous solution was evenly scraped on the surface of the activated carbon / polyvinyl alcohol composite hydrogel, allowed to stand and level, frozen at -20 °C for 12 h and then melted at 25 °C for 2 h. The freeze-thaw step was repeated 5 times, and then freeze-dried for 24 h and rehydrated in phosphate buffer at 20-35 °C to obtain an asymmetric porous double-layer composite hydrogel PVA / PVA-AC10.
[0028] Example 3 This embodiment provides a method for preparing an asymmetric porous double-layer composite hydrogel, comprising the following steps: (1) Add 10 g of polyvinyl alcohol to 90 g of water, stir and mix at 90-100 °C to obtain a 10% polyvinyl alcohol aqueous solution; (2) 1 g of medicinal activated carbon was mixed with 50 g of 10% polyvinyl alcohol aqueous solution at 12000 rpm for 15 min, poured into a mold, and frozen at -20 °C for 12 h to obtain activated carbon / polyvinyl alcohol composite hydrogel PVA-AC20; (3) 3 g of activated carbon / polyvinyl alcohol composite hydrogel PVA-AC20 was melted at 20-30 °C for 1-3 h, and then 1 g of 10% polyvinyl alcohol aqueous solution was evenly scraped on the surface of the activated carbon / polyvinyl alcohol composite hydrogel, allowed to stand and level, frozen at -20 °C for 12 h and then melted at 25 °C for 2 h. The freeze-thaw step was repeated 5 times, and then freeze-dried for 24 h and rehydrated in phosphate buffer at 20-35 °C to obtain an asymmetric porous double-layer composite hydrogel PVA / PVA-AC20.
[0029] Comparative Example 1 This comparative example provides a method for preparing a PVA composite hydrogel, comprising the following steps: (1) Add 10 g of polyvinyl alcohol to 90 g of water, stir and mix at 90-100 °C to obtain a 10% polyvinyl alcohol aqueous solution; (2) 50 g of 10% polyvinyl alcohol aqueous solution was mixed under high-speed stirring at 12,000 rpm for 15 min, poured into a mold, and frozen at -20 °C for 12 h to obtain PVA hydrogel; (3) Thaw 3 g of PVA hydrogel at 20-30 °C for 1-3 h, then evenly spread 1 g of 10% polyvinyl alcohol aqueous solution on the surface of the PVA hydrogel, let it stand to level, freeze it at -20 °C for 12 h, and then thaw it at 25 °C for 2 h. Repeat the freeze-thaw step 5 times, then freeze-dry it for 24 h and rehydrate it in phosphate buffer at 20-35 °C to obtain the PVA composite hydrogel.
[0030] In order to better illustrate the technical effects of the present application, the PVA composite hydrogel prepared in Comparative Example 1, PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 prepared in Examples 1-3 were subjected to morphological characterization, swelling rate experiments, in vitro ROS removal experiments, cell compatibility experiments, cell adhesion experiments, and animal experiments.
[0031] Effect Example 1 In this effect example, the morphology of PVA / PVA-AC10 prepared in Example 2 was characterized by scanning electron microscopy. The results are as follows Figure 1 As shown. Figure 1 It can be seen that PVA / PVA-AC10 has a double-sided asymmetric structure, the dense porous surface is dense and smooth, with a pore size distribution of 0.5-2 μm, and the loose porous surface is loose and porous, with a pore size greater than 10 μm.
[0032] Effect Example 2 This effect example uses the weighing method to measure the swelling rate of the PVA composite hydrogel prepared in Comparative Example 1, and the PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 prepared in Examples 1-3. The specific test method is: PVA, PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 are divided into 4 groups, each with 4 samples, and after rehydration with PBS for 24 hours, the surface moisture is wiped off, and the wet mass of the sample is weighed and recorded as w 0 , sterilized by ultraviolet for 30 minutes, operated in a clean bench, added 3 mL PBS buffer to each sample, placed in a 37 °C shaker, took out the samples on days 7, 14, 21, and 28, wiped off the surface moisture, weighed them, and recorded w t The swelling ratio is recorded as Δw and is calculated according to the following formula.
[0033]
[0034] The results are as follows Figure 2As shown in the figure, the introduction of activated carbon can improve the anti-swelling performance of PVA hydrogel, and the higher the activated carbon content, the lower the swelling rate of the hydrogel.
[0035] Effect Example 3 This effect example uses the PVA composite hydrogel prepared in Comparative Example 1, and the PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 prepared in Examples 1-3 to perform an in vitro ROS removal experiment. The specific test method is: immerse 15 mm*15 mm*1 mm PVA, PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 in 2 mL DPPH ethanol solution, and shake the solution in the dark (120 rpm, 37 ° C). After a predetermined time, the absorbance at 515 nm is measured using a UV-visible spectrometer. The DPPH removal efficiency of the sample is calculated according to the formula.
[0036]
[0037] The results are as follows Figure 3 As shown, PVA / PVA-AC10 and PVA / PVA-AC20 have excellent DPPH adsorption performance, and the DPPH removal efficiency exceeds 90% within 48 hours.
[0038] Effect Example 4 In this effect example, the commercial PCO patch (Cohui), the PVA composite hydrogel prepared in Comparative Example 1, and the PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 prepared in Examples 1 to 3 were subjected to a cell compatibility experiment. The specific test method is: after PCO, PVA, PVA / PVA-AC5, PVA / PVA-AC10 and PVA / PVA-AC20 were co-cultured with L929 fibroblasts for 1, 2, and 3 days, the proliferation activity was detected by the CCK-8 method.
[0039] The results are as follows Figure 4 As shown, the growth trend of cells in each group was good, and there was no significant difference among the groups on days 1, 2, and 3. This indicates that PVA / PVA-AC5, PVA / PVA-AC10, and PVA / PVA-AC20 do not affect the proliferation activity of cells and have good cell compatibility.
[0040] Effect Example 5 In this effect example, commercial PCO patch (Cohui), PVA composite hydrogel prepared in comparative example 1, and PVA / PVA-AC10 prepared in example 2 were subjected to cell adhesion experiment. The specific test method is: 4 parallel experiments are set up for PCO collagen surface, PVA dense porous surface and loose porous surface, PVA / PVA-AC10 dense porous surface and loose porous surface, the samples are sterilized by ultraviolet light for 1 hour and then placed in a well plate, and then 4 x 10 5 Cell / well density: L929 mouse fibroblasts were inoculated on the sample, and the well plate was placed in a 37 ℃, 5% carbon dioxide incubator for 48 h. The culture medium was removed and the plate was gently washed three times with PBS. Calcein AM live-dead fluorescent dye was added and incubated in the dark for 15 min. The cell adhesion was observed and photographed under an inverted fluorescence microscope.
[0041] The results are as follows Figure 5 As shown in the figure, there were only a small amount of cell adhesion on the PCO collagen surface, PVA dense porous surface, and PVA / PVA-AC10 dense porous surface, showing good anti-cell adhesion performance; while there were more cells adhesion on the PVA / PVA-AC10 loose porous surface than on the PVA loose porous surface, indicating that the introduction of activated carbon has a good promoting effect on cell proliferation and adhesion.
[0042] Effect Example 6 This effect example uses commercial PP patch (Zhonghui Shengxi), commercial PCO patch (Kehui), PVA composite hydrogel prepared in comparative example 1, and PVA / PVA-AC10 prepared in Example 2 for animal experiments. The specific test method is: construct an animal model of abdominal wall defect in rats, all rats are anesthetized by intraperitoneal injection of sodium pentobarbital in the anesthesia room, and a circular defect with a diameter of 1 cm is formed in the middle of the abdominal wall by a standard biopsy punch under aseptic surgical techniques. The peritoneum and full-thickness abdominal wall muscles are removed, but the skin is completely retained, and the PP patch, PCO patch, PVA hydrogel, and PVA / PVA-AC10 hydrogel are sutured to repair the defect, and then the wound is sutured. The animals were humanely euthanized on the 10th and 28th days after surgery in accordance with the guidelines of the Animal Welfare Act. After skin peeling, the sutures were reopened to expose the repaired site to evaluate the formation of adhesions and the results of defect healing.
[0043] The results are as follows Figure 6 As shown in the figure, PVA / PVA-AC10 has a good effect in preventing visceral adhesion and is superior to the PP patch and PCO patch commonly used in clinical practice.
[0044] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. An asymmetric porous double-layer composite hydrogel, characterized in that: The asymmetric porous double-layer composite hydrogel comprises a first hydrogel layer and a second hydrogel layer, wherein the first hydrogel layer is a polyvinyl alcohol hydrogel layer, and the second hydrogel layer is an activated carbon / polyvinyl alcohol composite hydrogel layer; The asymmetric porous double-layer composite hydrogel has a double-sided asymmetric structure, including a loose porous surface and a dense porous surface.
2. A method for preparing an asymmetric porous double-layer composite hydrogel, characterized in that: Used to prepare the asymmetric porous double-layer composite hydrogel as claimed in claim 1; The preparation process includes the following steps: (1) dissolving polyvinyl alcohol in water, and stirring to obtain a polyvinyl alcohol aqueous solution; (2) adding activated carbon to the polyvinyl alcohol aqueous solution and stirring to mix evenly, and freezing to obtain an activated carbon / polyvinyl alcohol composite hydrogel; (3) The activated carbon / polyvinyl alcohol composite hydrogel prepared in step (2) is allowed to stand and melt, and the polyvinyl alcohol aqueous solution obtained in step (1) is evenly scraped on the surface of the melted activated carbon / polyvinyl alcohol composite hydrogel, and the mixture is allowed to stand and level, and then the activated carbon / polyvinyl alcohol composite hydrogel with the polyvinyl alcohol aqueous solution evenly scraped on the surface is repeatedly freeze-thawed, and then freeze-dried and rehydrated in phosphate buffer to obtain an asymmetric porous double-layer composite hydrogel.
3. The method for preparing the asymmetric porous double-layer composite hydrogel according to claim 2, characterized in that: In the step (1), the mass fraction of the polyvinyl alcohol aqueous solution is 5% to 15%.
4. The method for preparing the asymmetric porous double-layer composite hydrogel according to claim 2, characterized in that: In the step (2), the mass ratio of activated carbon to the polyvinyl alcohol aqueous solution is (0.5-2):
100.
5. The method for preparing the asymmetric porous double-layer composite hydrogel according to claim 2, characterized in that: In the step (3), the mass ratio of the coated polyvinyl alcohol aqueous solution to the activated carbon / polyvinyl alcohol composite hydrogel is 1:(3-4).
6. The method for preparing the asymmetric porous double-layer composite hydrogel according to any one of claims 2 to 5, characterized in that: In the step (1), the polyvinyl alcohol aqueous solution is prepared by stirring and mixing at 90-100°C.
7. The method for preparing the asymmetric porous double-layer composite hydrogel according to any one of claims 2 to 5, characterized in that: In the step (2), the mesh size of the activated carbon is 100-400 mesh; The step of stirring and mixing uniformly is: stirring at a speed of 10000-13000 r / min for 10-20 min.
8. The method for preparing the asymmetric porous double-layer composite hydrogel according to any one of claims 2 to 5, characterized in that: In the step (2), the activated carbon / polyvinyl alcohol composite hydrogel is prepared by freezing at -30 to -10°C for 10 to 16 hours.
9. The method for preparing an asymmetric porous double-layer composite hydrogel according to any one of claims 2 to 5, characterized in that: In the step (3), the activated carbon / polyvinyl alcohol composite hydrogel prepared in the step (2) is melted at 20-30°C for 1-3 h, and the polyvinyl alcohol aqueous solution is evenly scraped on the surface of the melted activated carbon / polyvinyl alcohol composite hydrogel, and the mixture is left to stand and leveled. Subsequently, the activated carbon / polyvinyl alcohol composite hydrogel with the polyvinyl alcohol aqueous solution evenly scraped on the surface is frozen at -30--10°C for 10-16 h, and melted at 20-30°C for 1-3 h. The freezing-thawing step is repeated 3-5 times, and then freeze-dried for 22-26 h and rehydrated in phosphate buffer at 20-35°C to prepare the asymmetric porous double-layer composite hydrogel.
10. Use of the asymmetric porous double-layer composite hydrogel as claimed in claim 1 in biomedical materials.
Citation Information
Patent Citations
Double-layer bionic drug-loaded hydrogel as well as preparation and application thereof
CN115124738A
Porous membrane material with active healing promoting function as well as preparation method and application of porous membrane material
CN116672513A
Preparation method of abdominal wall defect repair material
CN117398527A